The Effectiveness of Giving Fe Tablets with Tomato Juice on Hemoglobin Levels in Third Trimester Pregnant Women with Anemia - Bunga Tiara Carolin; Vivi Silawati; Siti Nurendah; Shinta Novelia (Nursing and Health Sciences Journal (NHSJ), 2023)
Based on Riskesdas data in 2018, it was reported that the incidence of anemia in pregnant women in Indonesia nationally was 48.9%. The prevalence of anemia is still high. This is also influenced by the pattern of consumption of iron tablets which is not supported by the fulfillment of vitamin C which is very helpful in the process of iron absorption. The objective: to determine the effectiveness of giving Fe tablets with tomato juice to increase hemoglobin levels in third trimester pregnant women with anemia. This quasi-experimental method uses a two-group pre-test-post-test design. The sample in this study amounted to 30 respondents consisting of 15 respondents each of the intervention group with purposive sampling technique. Data were analyzed using Paired T-test and Independent T-test. Univariate results showed that the average hemoglobin level of pregnant women in the intervention group pretest was 9.94, and posttest was 10.80 with a p value of 0.000. The average hemoglobin level of pregnant women in the pretest control group was 9.99 and the posttest was 10.36 with a p value of 0.000. Bivariate results with independent t-test obtained p value 0.008. There are differences in the effectiveness of giving Fe tablets with Tomato Juice on Hemoglobin Levels in Third Trimester Pregnant Women with Anemia. It is expected to consume tomato juice or similar foods as an alternative to vitamin C combined with Fe tablets in an effort to increase hemoglobin levels in pregnant women.